Menghadapi Ajaran Sesat - Zevania Venda Andaline; Juanda Juanda (Jurnal Teologi dan Pelayanan Kerusso, 2019)
Since the appearance of the church, heresy has also begun to run rampant. The problem the same, also being faced by the church in this century. In Ephesians, Christians get attacks from both Jewish and Greek traditions at that time. Starting from Gnostic influence is also the god's worship. Then it is necessary to take a stand to see the situation like this, considering that if left unchecked it will damage the faith the church of God at that time. Then through Timothy's letter, Paul wanted to advise how to deal with avoiding superstition, faithful worship, full hope to God, teaches the true teachings and sets an example in the spiritual life.